Pengharuh Work Engagement dan Work Environment terhadap Job Performance melalui Creativity sebagai variabel mediasi Karyawan Bank X di Kota Surabaya - Hayaswari, Dinda Brilianti Eghi; Budiono (Universitas Negeri Surabaya, 2025)
Currently, global competition and increased productivity are important issues to discuss if you want to gain a competitive advantage and compete in similar businesses. To achieve a competitive advantage, the role of human resources greatly influences the results and final goals that must be achieved by the company. One of the main objectives of human resource management in business is to create high employee performance. The purpose of this study is to analyze the effect of work engagement and the work environment on employee performance with creativity as an intervening variable. This research is a causality study with a quantitative approach. The sampling technique used a saturated sample of Bank X employees with a total of 37 respondents at Bank X in Surabaya City. The statistical analysis used in this study is partial least squares (PLS) SmartPLS 3.2.9. Work engagement has a significant effect on employee performance. The work environment does not have a significant effect on employee performance. Creativity has a positive and significant effect on employee performance. Work engagement does not have a significant effect on creativity. The work environment has a positive and significant effect on creativity. Creativity does not mediate the effect of work engagement and the work environment on employee performance.